5-Aril-isoxazóis – síntese e aplicação como modelos para estudos supramoleculares - Longhi, Kelvis (2014)
This work describes the synthesis and halogenation of isoxazoles, and its application as a model for investigating complexities in the self-organization of molecules at the supramolecular level, demonstrating that the design of the crystal originates through the emergence of several intermolecular interactions. 5-aryl-isoxazoles were synthesized without solvent by Grindstone Chemistry method in good yields and low reaction time. Two methodologies (conventional and ultrasound radiation) were used to obtain the series of 5-aryl-4-haloisoxazoles from the halogenation of the precursor with N-halosuccinimides (NCS, NBS and NIS). Ultrasound irradiation was more effective for this synthesis, since the products were obtained in lower reaction times and high yields. For iodination with NIS, trifluoracetic acid as a catalyst was necessary. All synthesized compounds were characterized by 1H and 13C NMR, and mass spectrometry. The compounds obtained as crystals were studied at the molecular and supramolecular structural level. The characterization at the molecular level was performed through geometrical x-ray diffraction data, regions of low and high electronic density (electrostatic potential maps), and regions of the intermolecular contacts by Hirshfeld surface. Characteristic patterns were identified from this first analysis. The supramolecular structure was studied through the generation of clusters of the first coordination sphere, where it was possible to identify each of the Mn molecules that constitute the respective clusters, and determine the molecular coordination number (prevalence of 13 and 14). Subsequently, the dimers formed by the molecules M1 and Mn were characterized by areas and energies of contact in CrystalExplorer® and TOPOS® programs, and Gaussian 09 program package (B97D/cc-pVTZ level DFT), respectively. Good linearity was found in both characterizations, showing a strong dependence on the contact area for the respective interactions between molecules. The analysis of these dimers revealed the presence of polarization effects induced by an intermolecular bond on neighboring molecules, and the presence of dimers that had a greater contribution in the cluster, demonstrating the existence of complementarity and cooperation in the stabilization all of the clusters. The robustness of the molecule...molecule interaction was determined by energy and contact normalized data, demonstrating that weak hydrogen bonds can be considered robust in these compounds. The study concludes with a proposal for the process of self-organization of molecules through the formation of robust dimers. Thus, it was possible to infer based on energy data that π...π interactions attract the molecules at a stage prior to crystallization, namely, in solution, while the influence of other types of interactions may occur later.